2014
DOI: 10.1042/bst20130281
|View full text |Cite
|
Sign up to set email alerts
|

cAMP signalling meets mitochondrial compartments

Abstract: Mitochondria are highly dynamic organelles comprising at least three distinct areas, the OMM (outer mitochondrial membrane), the IMS (intermembrane space) and the mitochondrial matrix. Physical compartmentalization allows these organelles to host different functional domains and therefore participate in a variety of important cellular actions such as ATP synthesis and programmed cell death. In a surprising homology, it is now widely accepted that the ubiquitous second messenger cAMP uses the same stratagem, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…This finding raises a number of intriguing questions, e.g., whether there is a specific subcellular location, where sAC-mediated cAMP synthesis and PKA activation occur during cholesterol repletion of hepatocytes. A previous study showed that sAC co-localizes with mitochondria in multiple cell types (Lefkimmiatis, 2014;Valsecchi et al, 2013), and mitochondria are known to associate with regions of the ER, termed mitochondria-associated membranes (MAMs) that are rich in IP3Rs (Wieckowski et al, 2009). cAMP acts locally to activate nearby PKA, which is anchored by AKAP in discrete microdomains (Rich et al, 2000;Zaccolo and Pozzan, 2002).…”
Section: Article Discussionmentioning
confidence: 99%
“…This finding raises a number of intriguing questions, e.g., whether there is a specific subcellular location, where sAC-mediated cAMP synthesis and PKA activation occur during cholesterol repletion of hepatocytes. A previous study showed that sAC co-localizes with mitochondria in multiple cell types (Lefkimmiatis, 2014;Valsecchi et al, 2013), and mitochondria are known to associate with regions of the ER, termed mitochondria-associated membranes (MAMs) that are rich in IP3Rs (Wieckowski et al, 2009). cAMP acts locally to activate nearby PKA, which is anchored by AKAP in discrete microdomains (Rich et al, 2000;Zaccolo and Pozzan, 2002).…”
Section: Article Discussionmentioning
confidence: 99%
“…Matrix-localized, HCO 3 − -regulated sAC generates cAMP which increases electron transport chain and OXPHOS activities, resulting in increased ATP production [20]. Thus, CO 2 -dependent sAC activity links TCA cycle flux with OXPHOS activity [83,87,88]. In addition to CO 2 -dependent regulation, this intramitochondrial sAC signalling cascade is responsive to calcium released from intracellular stores [21,84].…”
Section: Sac Also Functions As a Carbon Dioxide And Ph Sensormentioning
confidence: 99%
“…sAC was found to reside inside the mitochondrial matrix where it de-fines a cAMP microdomain which couples activity of the Krebs cycle with flux through the electron transport chain and ATP generation (Di Benedetto, Gerbino, & Lefkimmiatis, 2017; Lefkimmiatis, 2014; Lefkimmiatis & Zaccolo, 2014; Valsecchi, Konrad, & Manfredi, 2014; Valsecchi, Ramos-Espiritu, Buck, Levin, & Manfredi, 2013). The Krebs cycle produces the electrons which feed the electron transport chain to create the electrochemical gradient which drives ATP production.…”
Section: Physiological Roles Of Sac Identified Using Sac Inhibitorsmentioning
confidence: 99%
“…sAC is found distributed through the cytoplasm and in cellular organelles (Acin-Perez et al, 2009; Di Benedetto, Scalzotto, Mongillo, & Pozzan, 2013; Lefkimmiatis, 2014; Lefkimmiatis, Leronni, & Hofer, 2013; Lefkimmiatis & Zaccolo, 2014; Valsecchi, Konrad, & Manfredi, 2014; Valsecchi, Ramos-Espiritu, Buck, Levin, & Manfredi, 2013; Zippin et al, 2003; Zippin et al, 2004; Zippin, Chadwick, Levin, Buck, & Magro, 2010), including inside the nucleus (Zippin et al, 2004; Zippin, Chadwick, Levin, Buck, & Magro, 2010) and the mitochondrial matrix (Acin-Perez et al, 2011; Acin-Perez, Salazar, Kamenetsky, et al, 2009; Zippin et al, 2003). Inside the matrix, the sAC-defined intramitochondrial cAMP signaling cascade regulates ATP production (Acin-Perez, Salazar, Kamenetsky, et al, 2009; Di Benedetto, Scalzotto, Mongillo, & Pozzan, 2013; Lefkimmiatis, 2014; Lefkimmiatis, Leronni, & Hofer, 2013; Lefkimmiatis & Zaccolo, 2014). In the cytoplasm, sAC has been identified as the AC responsible for the cAMP regulating lysosomal acidification (Rahman, Ramos-Espiritu, Milner, Buck, & Levin, 2016), apoptosis (Ladilov & Appukuttan, 2014), and the downstream effects from the trafficking GPCRs corticotropin-releasing hormone receptor (Inda et al, 2016, 2017).…”
Section: Introductionmentioning
confidence: 99%